Therapeutic effects and long-term outcomes of HMGB1-targeted therapy in rats and mice with traumatic spinal cord injury: A systematic review and meta-analysis - Deng, Chen; Deng, Li; Lv, Junqiao; Sun, Lin (Frontiers in Neuroscience, 2022)
Background: To date, the clinical need for therapeutic methods to prevent injury progression and improve functional recovery has not been met. High mobility group box-1 (HMGB1) is released by necrotic neurons or secreted by glial cells after SCI and plays an important role in pathophysiology. Objective: The purpose of this study was to evaluate the effects of HMGB1-targeted therapy on locomotor function recovery, inflammation reduction, edema attenuation, and apoptosis reduction in rat and mice models of spinal cord injury. Methods: We reviewed the literature on HMGB1-targeted therapy in the treatment and prognosis of SCI. Twelve articles were identified and analyzed from four online databases (PubMed, Web of Science, Cochrane Library and Embase) based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and strict inclusion criteria. Results: The methodological quality of the 12 articles was poor. The results of the meta-analysis showed that compared with the SCI group, the treatment group had significantly increased locomotor function scores after SCI (n = 159, standardized mean difference (SMD) = 2.31, 95% confidence interval (CI) [1.52, 3.10], P < 0.00001), and the change in locomotor function scores was significantly increased in both the drug and anti-HMGB1 Ab groups (P<0.000001 and P<0.000001). A subgroup analysis showed significant differences (P>0.05) between the drug group ((SMD)=1.95, 95% CI [0.95, 2.94], P=0.0001) and the anti-HMGB1 Ab group ((SMD)=2.89, 95% CI [1.66, 4.13], P<0.00001). Compared with the SCI group, HMGB1 expression was significantly diminished (n = 76, SMD = -2.31, 95% CI [-3.71, -0.91], P=0.001), TNF-α levels were significantly reduced (n = 76, SMD =-2.52, 95% CI [-3.77, -1.27], P < 0.0001), water content was significantly reduced (n = 44, SMD = -3.94, 95% CI [-6.28, -1.61], P = 0.0009), and the number of apoptotic cells was significantly diminished (n = 36, SMD = -3.31, 95% CI [-6.40, -0.22], P = 0.04) in the spinal cord of the treatment group. Conclusions: HMGB1-targeted therapy improves locomotor function, reduces inflammation, attenuates edema, and reduces apoptosis in rat and mice models of spinal cord injury. Intrathecal injection of anti-HMGB1 Ab immediately after SCI was the most efficacious treatment.